Answered

Welcome to Westonci.ca, your ultimate destination for finding answers to a wide range of questions from experts. Get the answers you need quickly and accurately from a dedicated community of experts on our Q&A platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.

give h (x) = 2x + 5, find h (-6)


Sagot :

Answer:

[tex]h(-6) = - 7[/tex]

Step-by-step explanation:

Basically, with a function, we just plug whatever this number is: h(x) into every other x in the equation. So we plug -6 into every x in the equation: 2x + 5.

h(-6) = 2(-6) + 5

h(-6) = -12 + 5

h(-6) = -7